2015
DOI: 10.1016/j.bmc.2015.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Modification of cellular DNA by synthetic aziridinomitosenes

Abstract: Two synthetic aziridinomitosenes (AZMs), Me-AZM and H-AZM, structurally related to mitomycin C (MC) were evaluated for their anticancer activity against six cancer cell lines (HeLa, Jurkat, T47D, HepG2, HL-60, and HuT-78) and tested for their DNA-modifying abilities in Jurkat cells. Cytotoxicity assays showed that Me-AZM is up to 72-fold and 520-fold more potent than MC and H-AZM, respectively. Me-AZM also demonstrated increased DNA modification over MC and H-AZM in alkaline COMET and Hoechst fluorescence assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The activated species generated ( 13 or 14 ) determine the outcome of DNA alkylation both with DNA extract and within cells [11]. Although all mitomycin C-DNA adducts obtained upon reductive activation have been isolated and characterized, questions remain regarding the activation and the reactivity of both mitomycins [21] and aziridinomitosenes [22]. …”
Section: Resultsmentioning
confidence: 99%
“…The activated species generated ( 13 or 14 ) determine the outcome of DNA alkylation both with DNA extract and within cells [11]. Although all mitomycin C-DNA adducts obtained upon reductive activation have been isolated and characterized, questions remain regarding the activation and the reactivity of both mitomycins [21] and aziridinomitosenes [22]. …”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the anticancer activity of the DIDOX analogs, several different cell lines were employed in cytotoxicity assays. Specifically, all the analogs, DIDOX, and DOX were subjected to a series of resazurin reduction assays-results of which are shown in Table 2.1-to compare antiproliferative activity (Mallory, 2015). This assay followed the reduction of non-fluorescent blue resazurin to fluorescent pink resorufin, which only occurs in healthy and metabolically active cells.…”
Section: In Vitro Cytotoxicity Results Of Didox Analogsmentioning
confidence: 99%
“…A resazurin reduction assay was used to determine the cytotoxicity of DOX, DIDOX, and DIDOX analogs against an array of cancer lines (Mallory, 2015). Cells were washed with 1x PBS three times and suspended in trypsin-EDTA while incubating at 37 °C for five minutes.…”
Section: In Vitro Assaysmentioning
confidence: 99%
“…Warner and coworkers reported that the synthetic AZMs 19 and 20 were able to form DNA crosslinks and DNA-protein adducts (DPCs) in Jurkat and HeLa cancer cells after one hour of treatment in an aerobic environment. 45 Cytotoxicity assays showed that 20 was up to 72 and 520 times more potent than MC and 19, respectively, against a variety of adherent and non-adherent cancer cell lines. The IC₅₀ values for MC and 19…”
Section: Reactivity and Cytotoxicity Of Synthetic Aziridinomitosenesmentioning
confidence: 99%